Parâmetros clínicos e laboratoriais relacionados ao prognóstico em cães com gastroenterite hospitalizados - Isola, José Geraldo Meirelles Palma [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Sepsis is a multifactorial syndrome with serious consequences for survival and costs of treatment in dogs. In this context gastroenteritis is an important representative of this inflammatory syndrome infectious association in the veterinary emergencies area. This single-center, prospective cohort study presented as a fundamental objective to identify the prognostic variables associated with survival in the short and medium term of 56 dogs with gastroenteritis treated in emergency and critical care hospital. Physiological and laboratory datas were collected on admission of emergency patients ( T0 ) and 24 hours later ( T24 ). Thus, the relationship between these parameters and the survival or mortality in 24 hours, and at 7, 30 and 60 days after admission were found. With the results, decision trees used in the stratification, prediction and identification of all possible interactions were created. The severity of the clinical, laboratory findings and historical background predicts mortality in canine patients with gastroenteritis , and patients diagnosed with parvovirus or hemorrhagic gastroenteritis, ranked in severe sepsis or septic shock, have higher mortality both at 24 hours as at 7, 30 and 60 days after treatment. The fall of potential oxygen transport, the oncotic potential and metabolic changes at the cellular level were determining the prognosis of patients, respectively represented by the high prognostic power of variations within 24 hours of hematocrit, total protein and lactate as well as presence of severe peripheral vasoconstriction 24 hours after initiation of treatment, as demonstrated by scores greater vasoconstriction. Thus, it is intended with this study, getting familiar to veterinarians to predict survival in dogs with gastroenteritis based on simple parameters, low cost and easy implementation

A sepse é uma síndrome de caráter multifatorial e com consequências graves para sobrevida e para os custos de tratamento em cães. Neste contexto a gastroenterite é um representante importante desta síndrome inflamatória de associação infecciosa no campo das urgências veterinárias. Este estudo unicêntrico, prospectivo e de coorte apresentou como objetivo fundamental identificar as variáveis prognósticas associadas com a sobrevivência a curto e médio prazo de 56 cães com gastroenterite, atendidos como urgências e hospitalizados para cuidados intensivos. Foram coletados dados fisiológicos e laboratoriais no momento da admissão de urgência dos pacientes (T0) e 24 horas depois (T24). Desta forma, foram encontradas as relações destes parâmetros com a sobrevivência ou a mortalidade em 24 horas, e aos 7, 30 e 60 dias pós ingresso. Com os resultados obtidos, foram criadas árvores de decisão empregadas na estratificação, previsão e identificação de todas as interações possíveis. A gravidade do quadro clínico, laboratorial e dos antecedentes históricos prediz a mortalidade de pacientes caninos com gastroenterite; e os doentes diagnosticados com parvovirose ou gastroenterite hemorrágica, classificados em sepse grave ou em choque séptico, possuem maior mortalidade tanto às 24 horas quanto aos 7, 30 e 60 dias após atendimento. A queda do potencial de transporte de oxigênio, do potencial oncótico e a alteração metabólica em nível celular foram determinantes no prognóstico dos pacientes, representados respectivamente pelo alto poder prognóstico das variações em 24 horas do hematócrito, das proteínas totais e do lactato sérico, bem como a presença de vasoconstrição periférica grave 24 horas após o início do tratamento, demonstrada pelo maior escore de vasoconstrição. Deste modo, pretendeu-se com este estudo, possibilitar o conhecimento aos Médicos Veterinários de ...
Keywords: Cão - Doenças; Gastroenterite; Emergencias medicas; Lactatos; Prognostico; Tratamento intensivo; Lactates